A preparation method of HVLP copper foil with improved seersucker defects and its products and applications
By adding grain refining agents such as N-acetylcysteine and soracetic acid to the electrolyte of HVLP copper foil, the problem of bubble yarn defects in HVLP copper foil during the preparation process is solved, and the smaller and more uniform grain size of copper foil is achieved, reducing the internal stress and the probability of bubble yarn defects, and improving the stability and pass rate of the product.
Patent Information
- Application Number
- CN202411717059.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-04-08
AI Technical Summary
The HVLP copper foil has bubble yarn defects during the preparation process, resulting in the limitation of product qualification rate and capacity release. The existing technology has not been effectively refined to specific sizes and microstructure analysis.
By adding grain refining agents such as N-acetylcysteine and sorylacetic acid to the electrolyte, synergistically reduce the surface tension of the cathode roller, evenly distribute the grain refining agent, hinder copper ion deposition, control the copper ion deposition speed during the electroplating process, and reduce the grain size difference of the copper foil.
It effectively reduces the internal stress of HVLP copper foil, improves the stability of copper foil, significantly reduces the probability of bubble yarn defects, and improves the product pass rate.
Smart Images

Figure BDA0005157103630000071 
Figure HDA0005157103640000011 
Figure HDA0005157103640000012
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electrolytes, and in particular to a preparation method of an HVLP copper foil for improving seersucker defects, and a product and application thereof. Background Art
[0002] As the demand for high-speed data transmission increases in industries such as artificial intelligence, data communications, and automotive electronics, the supply and demand of copper foil for high-end electronic circuits is increasingly insufficient. Among them, HVLP copper foil suitable for high-frequency and high-speed circuits has a bubblegum problem during the preparation process, which restricts the product qualification rate and production capacity release. In the investigation of the existing patents of companies in the industry, most of the information related to bubblegum defects is in lithium battery copper foil products, and the relevant patents for lithium battery copper foil bubblegum do not specify the specific size of bubblegum defects.
[0003] Patent Nos. CN105905657B and CN214277856U only provide a detection device for how to detect seersucker defects online. Patent No. CN109930180B introduces a foil-making machine that accurately controls the overall surface density of copper foil. By controlling the surface density, the seersucker of lithium battery copper foil is improved, but the degree of improvement is not introduced. Patent No. CN211400668U introduces a seersucker defect caused by working conditions during the roughening process and an improvement device, which is different from the seersucker mechanism described in the present invention. Patent No. CN115992375A introduces the improvement of lithium battery copper foil seersucker through an additive formula. The focus of the invention is only on reducing the grain size of the copper foil and thus improving the flatness of the foil surface. The uniformity of the grain size has not been studied and a microstructure analysis diagram has not been provided.
[0004] The full name of HVLP copper foil is very low profile copper foil. As the name implies, HVLP copper foil has extremely low roughness. In order to achieve the physical properties such as low roughness, tensile strength, and elongation, different additives need to be added to the electrolyte to change the copper foil deposition rate and grain size for control. At present, the HVLP copper foil additive formula wetting agent, leveling agent, and brightener can only refine the grains to a certain extent, making the rough surface of the HVLP copper foil uniform and flat, reaching a low level of roughness. However, from the analysis of microscopic crystals, the internal crystal structure size of the existing HVLP copper foil varies greatly, and the grain size will change after baking. Therefore, after natural aging, seersucker defects may appear, and the appearance does not meet customer requirements.
[0005] In view of the above situation, the present invention provides a method for preparing an HVLP copper foil with improved seersucker defects, and a product and application thereof. Summary of the invention
[0006] In order to solve the above technical problems, the present invention provides a method for preparing HVLP copper foil with improved seersucker defects, the steps are as follows:
[0007] (1) Preparing a primary electrolyte in advance;
[0008] (2) adding an additive to the primary electrolyte to obtain a secondary electrolyte;
[0009] (3) obtaining a raw foil by electrolysis in a secondary electrolyte, and obtaining a finished HVLP copper foil after a surface treatment process;
[0010] The additive in step (2) comprises one or both of N-acetylcysteine and thioacetic acid.
[0011] As an embodiment of the present invention, the components of the primary electrolyte include: a copper ion concentration of 90-98 g / L, a sulfate ion concentration of 210-230 g / L, a hydrogen ion concentration of 110-125 g / L, and a chloride ion concentration of 20-30 mg / L.
[0012] As an embodiment of the present invention, in the step (3), the secondary electrolyte is heated to 54° C. in a heat exchanger and filtered before participating in electrolysis, and then enters the electrolytic cell through a liquid supply system.
[0013] As an embodiment of the present invention, the electrolysis conditions in step (3) are: at 50A / dm 2 Electrolysis is carried out by a seamless cathode roller at a current density of .
[0014] As an embodiment of the present invention, in step (3), the copper ion concentration of the secondary electrolyte is 94 g / L, the hydrogen ion concentration is 120 g / L, and the chloride ion concentration is 25 mg / L.
[0015] As an embodiment of the present invention, the additive in step (2) further comprises one or more of a polyether compound, an organic sulfur compound, and a nitrogen-containing heterocyclic compound.
[0016] As an embodiment of the present invention, the additive in step (2) further comprises one or more of polyethylene glycol, polypropylene glycol, sodium phenyl polydisulfide propane sulfonate, 2-thiobenzimidazole, and benzotriazole.
[0017] As an embodiment of the present invention, the method for preparing the HVLP copper foil with improved seersucker defects is applied to the fields of electronics and electrical, new energy, and electronic equipment.
[0018] The present invention also provides a HVLP copper foil prepared by the preparation method.
[0019] The present invention also provides the HVLP copper foil, which is characterized by being applied to the fields of electronics and electrical, new energy, and electronic equipment.
[0020] By adopting the above technical solution, the present invention has the following beneficial effects:
[0021] 1. By introducing one or two of the grain refiners N-acetylcysteine and mercaptoacetic acid, the grain refiner and the other additives work synergistically, reducing the surface tension of the cathode roller, making the electrolyte more evenly distributed on the surface of the cathode roller, and increasing the uniformity of copper layer deposition. It can help carry the grain refiner evenly distributed in the entire electroplating area. The grain refiner hinders the deposition of copper ions in the electroplating area and reduces the cathode reaction rate to achieve the effect of reducing the grain size of the copper foil. The thiol structure in the grain refiner can inhibit the crystal growth in the raised area of the cathode roller or the copper foil and reduce the appearance of large grains. Furthermore, N-acetylcysteine and mercaptoacetic acid have a complexing effect, which can complex copper ions to make them more stable, help control the deposition rate of copper ions during the electroplating process, further reduce the grain size difference of the entire copper layer of the copper foil, and reduce the grain size difference of the HVLP copper foil throughout the thickness. The crystal structure with smaller size difference ensures that the internal stress of the copper foil is reduced during subsequent processing or natural placement, greatly reducing the probability of poplin defects.
[0022] 2. By introducing grain refiners, the grain size and uniformity of copper foil deposition are improved, thereby reducing the internal stress of the copper foil and improving the stability of the copper foil, thereby achieving the purpose of improving the defects of seersucker and improving the product qualification rate. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings in the following description are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0024] Figure 1 This is the SEM image of the rough surface of Example 1;
[0025] Figure 2 This is the cross-sectional EBSD image of Example 1;
[0026] Figure 3 This is the SEM image of the rough surface of Comparative Example 1;
[0027] Figure 4 is the cross-sectional EBSD image of comparative example 1;
[0028] Figure 5 This is the cross-sectional EBSD image of Example 1 after baking at 200°C for 1 hour;
[0029] Figure 6 This is the cross-sectional EBSD image of Comparative Example 1 after baking at 200°C for 1 hour. DETAILED DESCRIPTION
[0030] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] The present invention is further explained below in conjunction with specific implementation modes.
[0032] Example 1
[0033] This embodiment provides a method for preparing an HVLP copper foil with improved seersucker defects, and the steps are as follows:
[0034] (1) Adding a metal copper rod and a copper wire into a copper dissolving tank containing sulfuric acid to prepare a primary electrolyte, wherein the primary electrolyte comprises: a copper ion concentration of 90-98 g / L, a sulfate ion concentration of 210-230 g / L, a hydrogen ion concentration of 110-125 g / L, and a chloride ion concentration of 20-30 mg / L.
[0035] (2) Adding the following additives to the primary electrolyte to obtain a secondary electrolyte, the additives being: polyethylene glycol and polypropylene glycol at a concentration of 14 mg / L (the two are mixed in a mixing ratio of 3:5); phenyl polydisulfide propane sulfonate sodium at a concentration of 2 mg / L; 2-thiobenzimidazole and benzotriazole at a concentration of 20 mg / L (the two are mixed in a mixing ratio of 1:2); N-acetylcysteine and mercaptoacetic acid at a concentration of 10 mg / L (the two are mixed in a mixing ratio of 1:4); the copper ion concentration of the secondary electrolyte is 94 g / L, the hydrogen ion concentration is 120 g / L, the sulfate ion concentration is 214 g / L, and the chloride ion concentration is 25 mg / L; the secondary electrolyte is heated to 54°C by a heat exchanger and filtered by a precision filtration system (filter size is 0.45 μm), and then enters the electrolytic cell at 50 A / dm 2 At a current density of , the green foil is continuously prepared by electrolysis using a seamless cathode roller, and the prepared green foil is subjected to a surface treatment process to obtain a finished HVLP copper foil.
[0036] The surface treatment process is the standard treatment process, the specific process is as follows:
[0037] S1: The copper foil is pre-treated by pickling to clean the surface oxide layer. The concentration of sulfuric acid in the pickling solution is 140g / L
[0038] S2: Roughening treatment, copper ion concentration 11.5g / L, sulfuric acid concentration 140g / L, roughening solution temperature 27°C, roughening current density 25A / dm 2 , processing time 10s
[0039] S3: Curing treatment, copper ion concentration 50g / L, sulfuric acid concentration 100g / L, curing liquid temperature 50℃, curing current density 40A / dm 2 , processing time 10s
[0040] S4: Non-copper metal barrier layer electrodeposition
[0041] (1) Blackening treatment: nickel ion concentration 1.2 g / L, potassium pyrophosphate concentration 50 g / L, nickel plating electrolyte PH 10.1, temperature 40 °C, current density 0.45 A / dm 2 , nickel plating time 10s
[0042] (2) Ashing treatment: zinc ion concentration 1g / L, potassium pyrophosphate concentration 55g / L, zinc plating electrolyte pH 12, temperature 40°C, current density 0.5A / dm 2 , galvanizing time 10s
[0043] (3) Passivation treatment: chromium ion concentration 0.5g / L, chromium plating electrolyte pH 12.3, temperature 30°C, current density 0.75A / dm 2 , chrome plating time 10s
[0044] S5: Chemical bonding layer coating and drying, KBM-403 silane concentration 1250 mg / L, silane aqueous solution temperature 24°C, treatment time 10s, oven temperature 180°C, drying time 10s.
[0045] Example 2
[0046] This embodiment provides a method for preparing an HVLP copper foil with improved seersucker defects, and the steps are as follows:
[0047] (1) Adding a metal copper rod and a copper wire into a copper dissolving tank containing sulfuric acid to prepare a primary electrolyte, wherein the primary electrolyte comprises: a copper ion concentration of 90-98 g / L, a sulfate ion concentration of 210-230 g / L, a hydrogen ion concentration of 110-125 g / L, and a chloride ion concentration of 20-30 mg / L.
[0048] (2) Adding the following additives to the primary electrolyte to obtain a secondary electrolyte, the additives being: a mixture of polyethylene glycol and polypropylene glycol at a concentration of 16 mg / L, with a mass ratio of 3:5; a mixture of phenyl polydisulfide propane sulfonate at a concentration of 5 mg / L; a mixture of 2-thiobenzimidazole and benzotriazole at a concentration of 19 mg / L, with a mass ratio of 1:2; a mixture of N-acetylcysteine and mercaptoacetic acid at a concentration of 8 mg / L, with a mass ratio of 1:4; the copper ion concentration of the secondary electrolyte is 95 g / L, the hydrogen ion concentration is 116 g / L, the sulfate ion concentration is 211 g / L, and the chloride ion concentration is 26 mg / L; the secondary electrolyte is heated to 55° C. by a heat exchanger and filtered by a precision filtration system (filter size is 0.45 μm) into the electrolytic cell at 48 A / dm 2 At a current density of , the green foil is continuously prepared by electrolysis using a seamless cathode roller, and the prepared green foil is subjected to a surface treatment process to obtain a finished HVLP copper foil.
[0049] Example 3
[0050] (1) Adding a metal copper rod and a copper wire into a copper dissolving tank containing sulfuric acid to prepare a primary electrolyte, wherein the primary electrolyte comprises: a copper ion concentration of 90-98 g / L, a sulfate ion concentration of 210-230 g / L, a hydrogen ion concentration of 110-125 g / L, and a chloride ion concentration of 20-30 mg / L.
[0051] (2) Adding the following additives to the primary electrolyte to obtain a secondary electrolyte, the additives being: a mixture of polyethylene glycol and polypropylene glycol at a concentration of 18 mg / L, with a mass ratio of 3:5; a mixture of phenyl polydisulfide propane sulfonate at a concentration of 6 mg / L; a mixture of 2-thiobenzimidazole and benzotriazole at a concentration of 24 mg / L, with a mass ratio of 1:2; a mixture of N-acetylcysteine and mercaptoacetic acid at a concentration of 13 mg / L, with a mass ratio of 1:4; the copper ion concentration of the secondary electrolyte is 95 g / L, the hydrogen ion concentration is 114 g / L, the sulfate ion concentration is 210 g / L, and the chloride ion concentration is 24 mg / L; the secondary electrolyte is heated to 53° C. by a heat exchanger and filtered by a precision filtration system (filter size is 0.45 μm), and then enters the electrolytic cell at 55 A / dm 2 At a current density of , the green foil is continuously prepared by electrolysis using a seamless cathode roller, and the prepared green foil is subjected to a surface treatment process to obtain a finished HVLP copper foil.
[0052] Comparative Example 1
[0053] This embodiment provides a method for preparing an HVLP copper foil with improved seersucker defects, and the steps are as follows:
[0054] (1) Adding a metal copper rod and a copper wire into a copper dissolving tank containing sulfuric acid to prepare a primary electrolyte, wherein the primary electrolyte comprises: a copper ion concentration of 90-98 g / L, a sulfate ion concentration of 210-230 g / L, a hydrogen ion concentration of 110-125 g / L, and a chloride ion concentration of 20-30 mg / L.
[0055] (2) Adding the following additives to the primary electrolyte to obtain a secondary electrolyte, the additives being: a mixture of polyethylene glycol and polypropylene glycol at a concentration of 18 mg / L, with a mass ratio of 3:5; a mixture of phenyl polydisulfide propane sulfonate at a concentration of 6 mg / L; a mixture of 2-thiobenzimidazole and benzotriazole at a concentration of 24 mg / L, with a mass ratio of 1:2; the copper ion concentration of the secondary electrolyte is 95 g / L, the hydrogen ion concentration is 114 g / L, the sulfate ion concentration is 210 g / L, and the chloride ion concentration is 2 mg / L; the secondary electrolyte is heated to 53° C. by a heat exchanger and filtered by a precision filtration system, and then enters the electrolytic cell through a liquid supply system at 55 A / dm 2 At a current density of , the green foil is continuously prepared by electrolysis using a seamless cathode roller, and the prepared green foil is subjected to a surface treatment process to obtain a finished HVLP copper foil.
[0056] Comparative Example 2
[0057] (1) Adding a metal copper rod and a copper wire into a copper dissolving tank containing sulfuric acid to prepare a primary electrolyte, wherein the primary electrolyte comprises: a copper ion concentration of 90-98 g / L, a sulfate ion concentration of 210-230 g / L, a hydrogen ion concentration of 110-125 g / L, and a chloride ion concentration of 20-30 mg / L.
[0058] (2) Adding the following additives to the primary electrolyte to obtain a secondary electrolyte, the additives are: a mixture of polyethylene glycol and polypropylene glycol at a concentration of 18 mg / L, with a mass ratio of 3:5; a concentration of 6 mg / L phenyl polydisulfide propane sulfonate sodium; a concentration of 24 mg / L 2-thiobenzimidazole and a mixture of benzotriazole at a mass ratio of 1:2; a concentration of 10 mg / L N-acetylcysteine; the copper ion concentration of the secondary electrolyte is 95 g / L, the hydrogen ion concentration is 114 g / L, the sulfate ion concentration is 210 g / L, and the chloride ion concentration is 24 mg / L; the secondary electrolyte is heated to 53° C. by a heat exchanger and filtered by a precision filtration system (filter size is 0.45 μm), and then enters the electrolytic cell at 55 A / dm 2 At a current density of , the green foil is continuously prepared by electrolysis using a seamless cathode roller, and the prepared green foil is subjected to a surface treatment process to obtain a finished HVLP copper foil.
[0059] Comparative Example 3
[0060] (1) Adding a metal copper rod and a copper wire into a copper dissolving tank containing sulfuric acid to prepare a primary electrolyte, wherein the primary electrolyte comprises: a copper ion concentration of 90-98 g / L, a sulfate ion concentration of 210-230 g / L, a hydrogen ion concentration of 110-125 g / L, and a chloride ion concentration of 20-30 mg / L.
[0061] (2) Adding the following additives to the primary electrolyte to obtain a secondary electrolyte, the additives are: a mixture of polyethylene glycol and polypropylene glycol at a concentration of 18 mg / L, with a mixed mass ratio of 3:5; a concentration of 6 mg / L phenyl polydisulfide propane sulfonate sodium; a concentration of 24 mg / L 2-thiobenzimidazole and a mixture of benzotriazole at a mixed mass ratio of 1:2; a concentration of 10 mg / L mercaptoacetic acid; the copper ion concentration of the secondary electrolyte is 95 g / L, the hydrogen ion concentration is 114 g / L, the sulfate ion concentration is 210 g / L, and the chloride ion concentration is 24 mg / L; the secondary electrolyte is heated to 53°C by a heat exchanger and filtered by a precision filtration system (filter size is 0.45 μm), and then enters the electrolytic cell at 55 A / dm 2 At a current density of , the green foil is continuously prepared by electrolysis using a seamless cathode roller, and the prepared green foil is subjected to a surface treatment process to obtain a finished HVLP copper foil.
[0062] Performance Test:
[0063] The HVLP copper foil (specification 18 μm) prepared in the embodiment and the comparative example was subjected to performance tests, wherein the product is an electrolytic copper foil for printed circuit boards, and the relevant physical property test standards are in accordance with national standards.
[0064] Table 1 Physical properties of finished HVLP copper foil prepared in the examples and comparative examples and seersucker conditions
[0065]
[0066] Combined with Table 1, Appendix Figure 1-6 The analysis revealed that:
[0067] The additive process of Comparative Example 1 does not include a grain refiner. From the analysis of microscopic crystals, the crystal structure of Comparative Example 1 is mainly composed of a majority of block crystals with large grain sizes and a few columnar crystals. After baking, the sizes of the block crystals and columnar crystals are both increased. The crystal structure of the HVLP copper foil prepared by the traditional additive process is not stable enough, and it is easy to be affected by external forces or internal stresses during the copper foil processing to produce irreversible plastic deformation, forming seersucker defects.
[0068] It can be seen from the additive processes of Example 1, Example 2, and Example 3 that, on the basis of the combination of traditional additives, an additional grain refiner of appropriate concentration is introduced to change the microscopic crystal structure of the HVLP copper foil, and the crystal structure is changed from the previous mostly large-sized block crystals + columnar crystals to block crystals with smaller and more uniform grain size. In addition, the microscopic crystal size of the copper foil prepared by this method does not change much after high-temperature baking. The microscopic crystal structure of Examples 1-3 is stable, thereby improving the stability of the copper foil, and effectively improving the bubble yarn problem caused by the plastic deformation of the copper foil due to the microscopic crystal structure that cannot be recovered under the prior art.
[0069] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing HVLP copper foil with improved seersucker defects, characterized in that: Here are the steps: (1) Preparing a primary electrolyte in advance; (2) adding an additive to the primary electrolyte to obtain a secondary electrolyte; (3) obtaining a raw foil by electrolysis in a secondary electrolyte, and obtaining a finished HVLP copper foil after a surface treatment process; The additive in step (2) comprises one or both of N-acetylcysteine and thioacetic acid.
2. The method for preparing a HVLP copper foil with improved seersucker defects according to claim 1, characterized in that: The components of the primary electrolyte include: copper ion concentration of 90-98 g / L, sulfate ion concentration of 210-230 g / L, hydrogen ion concentration of 110-125 g / L, and chloride ion concentration of 20-30 mg / L.
3. The method for preparing a HVLP copper foil with improved seersucker defects according to claim 1, characterized in that: In the step (3), the secondary electrolyte is heated to 54° C. in a heat exchanger and filtered before entering the electrolytic cell through a liquid supply system before participating in electrolysis.
4. The method for preparing a HVLP copper foil with improved seersucker defects according to claim 1, characterized in that: The electrolysis conditions in step (3) are: at 50A / dm 2 Electrolysis is carried out by a seamless cathode roller at a current density of .
5. The method for preparing a HVLP copper foil with improved seersucker defects according to claim 1, characterized in that: In step (3), the copper ion concentration of the secondary electrolyte is 94 g / L, the hydrogen ion concentration is 120 g / L, and the chloride ion concentration is 25 mg / L.
6. The method for preparing a HVLP copper foil with improved seersucker defects according to claim 1, characterized in that: The additive in step (2) further comprises one or more of a polyether compound, an organic sulfur compound, and a nitrogen-containing heterocyclic compound.
7. The method for preparing a HVLP copper foil with improved seersucker defects according to claim 6, characterized in that: The additives in step (2) further include one or more of polyethylene glycol, polypropylene glycol, sodium phenyl polydisulfide propane sulfonate, 2-thiobenzimidazole, and benzotriazole.
8. The method for preparing HVLP copper foil with improved seersucker defects according to any one of claims 1 to 7, characterized in that: Applied in the fields of electronics and electrical, new energy, and electronic equipment.
9. A HVLP copper foil, characterized in that: The compound is prepared by the preparation method according to any one of claims 1 to 7.
10. The HVLP copper foil according to claim 9, characterized in that: Applied in the fields of electronics and electrical, new energy, and electronic equipment.
Citation Information
Patent Citations
Wavy pattern detection and correction equipment and its usage method
CN105905657B
A foil-making machine that can precisely control the overall surface density of copper foil.
CN109930180B
Production process for improving lithium battery copper foil seersucker
CN115992375A
Device for preventing coarsened foil seersucker
CN211400668U
Electrolytic copper foil seersucker detection equipment for lithium ion battery
CN214277856U